Orphanage Trafficking in Nepal: Legal Gaps, Protection Failures, and Reform Imperatives (The Informal: South Asian Journal of Human Rights and Social Justice, 2025)
This article examines the increasing phenomenon of orphanage trafficking in Nepal – a practice involving the coercive separation of children from their families and placement into unauthorized care facilities under false pretences, often for financial exploitation. Although the term “orphanage trafficking” is gaining traction both locally and internationally, it remains absent form Nepal’s formal legal framework. Employing a doctrinal approach, this paper evaluates relevant constitutional provisions, national child protection and antitrafficking legislation, and international obligations to assess Nepal’s compliance with its legal responsibilities. The analysis reveals significant gaps in constitutional and statutory protections, particularly concerning victim identification, unlawful removal from guardianship, and oversight of institutional care. These violations are frequently subsumed under the broad category of “violence against children”, undermining their recognition and prosecution as distinct forms of trafficking and exploitation. The article critiques the limited capacity of oversight institutions—including the National Child Rights Council and local child protection authorities—to identify victims, monitor facilities, and enforce standards. Highlighting these legal and systemic deficiencies, the paper calls for the formal recognition of orphanage trafficking within Nepal’s domestic law and stronger alignment with international standards. It concludes with targeted recommendations to address legislative shortcomings and enhance accountability for safeguarding vulnerable children